Impaired TrkB Signaling Underlies Reduced BDNF-Mediated Trophic Support of Striatal Neurons in the R6/2 Mouse Model of Huntington’s Disease - Nguyen, Khanh Q.; Rymar, Vladimir V.; Sadikot, Abbas F. (Frontiers in Cellular Neuroscience, 2016)
The principal projection neurons of the striatum are critically dependent on an afferent supply of brain derived neurotrophic factor (BDNF) for neurotrophic support. These neurons express TrkB, the cognate receptor for BDNF, which activates signaling pathways associated with neuronal survival and phenotypic maintenance. Impairment of the BDNF-TrkB pathway is suspected to underlie the early dysfunction and prominent degeneration of striatal neurons in Huntington Disease (HD). Some studies in HD models indicate that BDNF supply is reduced, while others suggest that TrkB signaling is impaired earlier in disease progression. It remains important to determine whether a primary defect in TrkB signaling underlies reduced neurotrophic support and the early vulnerability of striatal neurons in HD. Using the transgenic R6/2 mouse model of HD we found that prior to striatal degeneration there are early deficits in striatal protein levels of activated phospho-TrkB and the downstream-regulated protein DARPP-32. In contrast, total-TrkB and BDNF protein levels remained normal. Primary neurons cultured from R6/2 striatum exhibited reduced survival in response to exogenous BDNF applications. Moreover, BDNF activation of phospho-TrkB and downstream signal transduction was attenuated in R6/2 striatal cultures. These results suggest that neurotrophic support of striatal neurons is attenuated early in disease progression due to defects in TrkB signal transduction in the R6/2 model of HD.